NEGOTIATING THE PATH OF FAME: TRADITION AND MODERNITY IN THE PUBLIC PERSONA OF ROEKIAH (1917–1945) - Woodrich, Christopher Allen (Sanata Dharma University, 2017)
The first great dame of the Indonesian cinema, Roekiah, rose to fame just as the medium of film came into its own. Born in 1917, she, as with many of her contemporaries, had a background in stage and was renowned for her vocal abilities. Her first filmic role, in Albert Balink's Terang Boelan (1937), catapulted her to stardom. Over the next five years she appeared in a further eight films, first opposite Rd. Mochtar then Ismail Djoemala, becoming one of the colony's best-loved stars. In her personal life, Roekiah was married to Kartolo, and would often defer to him when speaking to reporters. The couple had five children. This paper examines how the damsel-in-distress roles played by Roekiah and her public persona as a demure and obedient wife positioned her between two ideals: the traditional woman and the modern woman. It argues that, by negotiating between these two ideals and emphasizing her traditional attributes, Roekiah was able to capitalize on the patriarchal society's views of women, thus enabling her to reach a level of success unattained by such contemporary actresses as Fifi Young, Hadidjah, and Ratna Asmara.DOI: https://doi.org/10.24071/ijhs.2017.010102